52 Retrospective analysis of the effectiveness of nurse-led clinic for patients post percutanous coronary intervention. (October 2018) - Ibrahim, A; Heelan, M; Coffey, J; McElligott, H; Coyne, C; Cahill, C; Mannix, K; Ahern, C; Kiernan, T
Abstract : Background: With an increasing global prevalence, of coronary heart disease, secondary prevention forms a major cornerstone of management. A dedicated nurse-led clinic for patients post percutanous coronary intervention (PCI) offers a great opportunity to address risk factors in order to reduce cardiovascular events. Purpose: To determine the effectiveness of nurse-led clinic follow up of patients post PCI and the rate of 28 day re-admission. Method: A retrospective review of parameters recorded at clinic appointments from January 2015- December 2017. The data of 1325 patients were examined for baseline characteristics, re-admission rates and interventions at their PCI clinic visits. Results: 1325 patients were reviewed in our nurse-led PCI clinic. Mean age was 64% and 78% were males. The main indications for PCI were ST- elevation myocardial infarction (STEMI) (22.7%), Non-STEMI (23%) and angina (43%) (table 1). At the clinic appointment, 852 (64.3%) patients were offered lifestyle advice or non-pharmacological intervention. The remainder 473 (35.70%) patients had appropriate pharmacological intervention (change in dose, addition or discontinuation of medications) (figure 1). 712 (53.7%) patients had LDL-C above recommended target and their statin therapy was amended accordingly. 132 patients (10%) were re-admitted within 28 days after the follow-up visit. However, only 23 (1.7%) were re-admitted due to cardiac reasons (figure 2). Conclusion: Nurse-led PCI clinics are a safe and effective option for follow-up of patients post PCI. They provide satisfactory assessment and management of risk factors without increased risk of poor outcomes.